Learning Disabilities and Low Social Status: The Role of Peer Academic Reputation and Peer Reputation of Teacher Liking. (May 2018) - van der Sande, Lisa; Hendrickx, Marloes M. H. G.; Boor-Klip, Henrike J.; Mainhard, Tim
Although many studies have found that children with learning disabilities (LD) are less liked by peers than children without LD, the results are not unequivocal. In the present study, we investigated the social status (in terms of likeability and popularity) of children with LD by considering peer academic reputation and peer reputation of teacher liking. These variables are potentially important alternative factors for differences in social status between children with and without LD. Fifth-grade students ( n = 1, 453; M age = 10.60) in 58 classes in the Netherlands completed peer nominations for academic reputation, teacher liking, and social status. The data were analyzed with Bayesian structural equation modeling. The associations between LD and social status were completely mediated by the lower peer academic reputation of children with LD. As expected, peer reputation of teacher liking served as a protective factor against low social status for children with low peer academic reputation in general but not specifically for children with LD. Implications for research and practice are discussed.